PENGARUH PERENCANAAN ANGGARAN DAN REALISASI BIAYA OPERASIONAL TERHADAP KINERJA PERUSAHAAN PADA PT. SOCFIN INDONESIA MEDAN - Suhendra, Jodhy Ashari; Rangkuti, Sahnan; Zahri, Cut (Universitas Dharmawangsa, 2024)
The fluency operation of the company supported by efficiency and effective use of operational fees will be sufficient to achieve optimal company performance. This research aims to determine the effect of budget planning and operational cost realization on company performance with PT. Socfin Indonesia Medan as a research locus. It is a multinational company located in Medan and operates in the agribusiness (Plantation) sector. This research uses quantitative methods with data collection techniques of interviews, observation and documentation studies. The data analysis technique uses multiple linear regression analysis methods, t-test, F test and coefficient of determination test. Based on the research results, it can be concluded that operational cost budget planning and operational cost realization affect the company's performance at PT. Socfin Indonesia Medan both partially and simultaneously. Furthermore, the research results also show that the company is still not precise in planning operational cost budgets and has not been optimal in managing operational costs.